The Influence of Audit Fees, Leadership Style, and Professionalism on Auditor Performance Through Auditor Experience as an Intervening Variable - F.DJ, Faradibha; Alam, Syamsu; Tenriwaru, Tenriwaru (Invoice : Jurnal Ilmu Akuntansi, 2024)
This research aims to find out whether the audit fee variables, leadership style and professionalism have a direct influence on auditor performance or are assisted by the intervening variable, namely experience. This research is quantitative. The research location was carried out at the Makassar City Public Accounting Office, South Sulawesi. The data source taken is the Primary data source. The data collection technique used by researchers is distributing questionnaires. Meanwhile, in analyzing the data, researchers used software, namely Smart PLS. The results of this research show that leadership style and professionalism have a positive and significant influence on auditor performance, audit fees have a positive but not significant influence on auditor performance. Audit fees have a positive and significant effect on experience, but leadership style and professionalism have a positive but not significant effect on experience. Experience has a negative and insignificant influence on auditor performance. Audit fees, leadership style and professionalism have a positive and significant influence on auditor performance through the experience variable as an intervening variable.